Aspectos gerais da vigilância entomológica da Doença de Chagas na Região Sul do Rio Grande do Sul, Brasil - Priotto, Maria da Conceição Monteiro (2012)
After the elimination of Triatoma infestans, Triatoma rubrovaria has been considered the main vector species of Trypanosoma cruzi in the household environment of Rio Grande do Sul. New knowledge about the distribution and biology of the insects are important, since such information can contribute to the control of these vectors. This study aimed to assess general aspects of entomological surveillance for Chagas disease in 22 municipalities in the southern Rio Grande do Sul (RS), which are supervised by the 3ª Coordination Regional Health of RS (3ªCRS), based in the Pelotas city. Evaluated the municipalities that have higher rates of capture, the main species, evolutionary stage and season with the highest catches. The study was conducted in collaboration with the 3ª CRS of RS, and occurred in from January 2010 to December 2011. Were recorded 148 notifications, by residents, in nine (40.9%) municipalities. The municipalities of Canguçu, Piratini, Santana da Boa Vista and Pinheiro Machado, accounted for 87.8% of these notifications. A total 295 triatomines were recorded in 148 captures. The species were Triatoma rubrovaria, Panstrongylus tupynambai, Triatoma circummaculata and Triatoma carcavalloi. All captures were made inside the home, which shows a higher risk of biting insects in the human population. The specimens were all dead and dry, unfavorable conditions find the protozoan in the digestive tract. It should enhance the captures of P. tupynambai and T. circummaculata indoors, because although there have already been identified in municipalities in the region, they have assumed greater importance and frequency in the households. Concerning seasonal aspects, in the months of January through April, considered the time of highest temperature, 257 bugs were reported, which corresponds to 87.1% of the encounters. It can be concluded that four species of bugs were found in the south of RS and T. rubrovaria it is the most captured, and the usual meeting place is the interior of the houses. The bugs invade rural households with relative frequency in this region, therefore the importance of health workers working in the Brazilian National Chagas Disease Control Program (PCDCh), it is important to communicate that the Program in the region is undergoing process of decentralization, the federal for municipal, which allowed the study to assess the difficulties of the agents and point out these suggestions for the best progress of the Program, and must always emphasize and enhance the entomological surveillance of this region.